Electronic prompt for capillary blood glucose monitoring in patients admitted for a fl are of infl ammatory bowel disease increases detection of steroid-induced diabetes. (2019) - Mitchell, Benjamin; Zare, Ben; Steane, Tilly; Abayalingam, Yathevan; Gwiggner, Markus
No abstract available